Lorazepam challenge test: A unique clinical response in catatonia - Aparna Seetharaman (Wolters Kluwer Medknow Publications, 2021)
Catatonia is a psychomotor behavioral syndrome characterized as a complex syndrome of bizarre motor behavior, impaired volition, and vegetative abnormalities. Catatonia is a medical emergency and if not recognized on time may have potentially fatal outcomes. We present a case series of three patients with catatonia, in whom Injection lorazepam 4 mg administered intravenously (Lorazepam Challenge) produced quick, optimum outcome.